Transforming lives via agroforestry: Breaking barriers through gender mainstreaming equality - Bohra, Babita; Choudhary, Rajendra; Singh, Rajkumar; Rizvi, Aqeel; Singh, Archna; Gallagher, Emily Jeanne; Rizvi, Javed; Dhyani, Shiv Kumar; Biradar, Chandrashekhar M. (CIFOR-ICRAF, 2023)
Gender equality and social-inclusion (GESI) integration is a key priority for CIFOR-ICRAF, reflecting its recognition of the vital role women play in the agriculture, forestry and agroforestry sectors vis-à-vis the barriers they encounter in this area owing to their roles and responsibilities. To address this disparity, CIFORICRAF is fully committed to mainstreaming gender considerations, raising awareness, and promoting inclusivity through gender-sensitive approaches and capacity building through training programs. Recently, ICRAF completed a four-year project for producing and consuming more nutritious food through agroforestry systems and is currently executing a project on sustainable production and application on biochar in two districts of Odisha that empowered women through self-help groups, raised awareness and built capacity through training in project interventions, including development of quality planting material, nurseries and others. As a result, these groups had a significant increase in their income, from earning Rs. 1,04,920 in 2019 to Rs. 1,69,180 in 2020. Furthermore, by carefully examining farmers’ views, knowledge, access and barriers linked to biochar production and use, both the projects incorporate gender-sensitive approaches. The projects use a participatory approach to craft activities to meet the specific needs and preferences of both men and women in agroforestry interventions and including the development of innovative biochar stoves. These stoves alleviate the burdens faced by women, reduce wood consumption, indoor pollution and greenhouse gas emissions, and result in drudgery reduction for women as well. Through this project, CIFOR-ICRAF hopes to advance gender equality, improve livelihoods, and support sustainable agriculture.